HUBUNGAN GROWTH MINDSET, ACADEMIC GRIT DENGAN MATHEMATICAL ENGAGEMENT PADA MAHASISWA PENDIDIKAN MATEMATIKA UIN RADEN INTAN LAMPUNG - Maria Ulfa, Despi; Netriwati; Niartahayuda, Gusti; Bagas Prasetyo, Adhi; Rifasafitri, Nabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between growth mindset, academic grit, and mathematical engagement among students in the Mathematics Education Program at Raden Intan State Islamic University, Lampung. The study adopted a quantitative correlational approach involving students as respondents. The research instruments were first tested for validity and reliability, resulting in items that were deemed valid and reliable. Normality tests indicated that the data were not fully normally distributed; therefore, data analysis was conducted using Spearman’s correlation test. The results showed that growth mindset had a positive and significant relationship with mathematical engagement (), while academic grit did not show a significant relationship with mathematical engagement . Furthermore, there is a strong relationship between growth mindset and academic grit (. These findings imply that a growth mindset plays a crucial role in enhancing students’ engagement in mathematics learning.